Lens disorders in degenerative myopia. Treatment options - M.H. Rabadanova; Zh.G. Oganezova; E.V. Kremkova; M.M. Yakh'yaeva (РМЖ "Клиническая офтальмология")
M.G. Rabadanova1,2, J.G. Oganezova1, E.V. Kremkova1, M.M. Yakh'yaeva1 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2O.M. Filatov City Clinical Hospital No. 15, Moscow, Russian Federation Cataracts are the leading cause of vision loss in patients over 50 years. In addition to senile cataracts, its earlier development due to various risk factors (for example, degenerative myopia characterized by lens opacity even in low myopia) is also an issue. This article discusses the pathogenesis of cataracts with a focus on oxidative stress, which is also important for myopia progression. The published and authors' data on the association between myopia and cataracts are addressed. The importance of early diagnosis of cataract in patients with myopia at the stage of lens suture compaction and its early radial and meridional opacities (that is possible with maximum mydriasis) is emphasized. Potential complex therapy with anti-cataract drops characterized by antioxidant effect is discussed as a pathogenetic approach to delay cataract progression in patients who (for various reasons) are not suitable for surgery. Recommendations for modifying the lifestyle to prevent cataract development are provided. Keywords: degenerative myopia, myopic cataract, lens, oxidative stress, antioxidants, risk factors, drug treatment, pirenoxine. For citation: Rabadanova M.G., Oganezova J.G., Kremkova E.V., Yakh'yaeva M.M. Lens disorders in degenerative myopia. Treatment options. Russian Journal of Clinical Ophthalmology. 2023;23(4):207–212 (in Russ.). DOI: 10.32364/2311-7729-2023-23-4-6.